ANALISIS FINGERPRINT DNA GENOTIPE BELIMBING DENGAN GENUS Averrhoa MENGGUNAKAN PRIMER RANDOM AMPLIFIED POLYMORPHIC - Nur Hikmah; Zahratul Idami; Kartika Manalu (Jurnal Biogenerasi, 2026)
Fingerprinting is a technique in DNA technology that can be used to see individual diversity and can also differentiate individuals from each other even though they are very closely related. This study aims to see the results of DNA fingerprinting of starfruit genotypes with the genus Averrhoa using Random Amplified Polymorphic DNA (RAPD) primers and to see the polymorphism value of each Random Amplified Polymorphic DNA (RAPD) primer. The research method used is Fingerprint DNA with Random Amplified Polymorphic DNA (RAPD) primers, namely OPA-2, OPA-3, OPA-5, OPA-7, OPD-11 and OPD-13. The results of the research show that the fingerprint results can be seen clearly. using electrophoresis. The best results were the primers OPA 2, OPA3 with 6 band patterns, followed by the second highest number of OPA5, OPD 11 with 5 band patterns, and the third highest number of OPA7, OPD 13 with 4 DNA fingerprint band patterns, the results of the kinship relationship between each Averrhoa have The polymorphic value shows that sweet starfruit (Averrhoa carambola L.) has a relationship of around 0.62% with starfruit. wuluh ( Averrhoa bilimbi L.). The Demak starfruit (Averrhoa carambola Cultivar Demak) has a relationship of around 0.71% with the Sembiring starfruit (Averrhoa carambola).